PEMANFAATAN KEONG TEMBERUNGUN (Telescopium-telescopium) SEBAGAI PAKAN ALTERNATIF TERHADAP PERTUMBUHAN DAN MOULTING KEPITING BAKAU (Scylla serrata) - Heppi Iromo, M.Si (Jurnal Harpodon Borneo, 2012)
Feeding with a balanced formulation of nutrition, can help the process of growth  and moulting of mub crab,Scylla serrata. In general, the Soca crab aquaculture  utilize  feed that is still competitive with humans thereby increasing the cost operasional, while in the intensive aquaculture require  the availability of feed in a number of good quality, inexpensive, sustainable and high production value. One of an alternative food for the growth of mud crab is  temberungun snail (Telescopium-telescopium), which is a waste of traditional farming in ponds. This study aimed to compare the effect of  temberungun snail as a feed with other feeds that high economic value for the  growth and moulting of mud crab. The research was carried on  January to May in traditional ponds in the small island of Tarakan. Four feed treatments were applied:  A = trash fish, B = temberungun snails (Telescopium-telescopium), C =  crustaceans (Penaeid sp), D = squid (Loligo sp).   The results of the studi showed that the use of   non-economical feed of  temberungun snail was not significantly different with the other natural feed that high economic value   to growth and moulting of mud crab. Keywords : Scylla serrata, growth, moulting, snail temberungun